2017
DOI: 10.1016/j.cmi.2017.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular assist device-related infections: a multicentric study

Abstract: 21Objectives. Implantable left ventricular assist device (LVAD) is a major therapeutic progress 22 for end-stage heart failure in selected patients. As their use is expanding, infectious 23 complications are emerging, with limited data available to guide their management. We 24 aimed to better characterize LVAD-related infections. 25Methods. We enrolled all consecutive patients diagnosed with LVAD-related infections in 3 26 referral centers in France, using standardized definition of infections in patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 15 publications
3
40
0
1
Order By: Relevance
“…Only postoperative RVF occurring during the index hospitalization following LVAD implantation was considered. Device infection is per criteria established by the Interagency Registry for Mechanically Assisted Circulatory Support (INTERMACS) [11]. Briefly, cutaneous site infections are defined as pain, erythema or purulent drainage at the driveline site with positive skin cultures.…”
Section: Methodsmentioning
confidence: 99%
“…Only postoperative RVF occurring during the index hospitalization following LVAD implantation was considered. Device infection is per criteria established by the Interagency Registry for Mechanically Assisted Circulatory Support (INTERMACS) [11]. Briefly, cutaneous site infections are defined as pain, erythema or purulent drainage at the driveline site with positive skin cultures.…”
Section: Methodsmentioning
confidence: 99%
“…A large prospective multicenter trial of 86 HeartMate II recipients identified depression and CKD as independent risk factors for infection [31], with adjusted hazard ratios of 2.8 (p = 0.007) and 1.7 (p = 0.023) respectively. A multicenter trial in France looked at 159 patients who received LVADs between 2007 and 2012 and found that 22.6% of the patients had at least one infectious complication [29]. LVAD infections in this cohort were associated with alcoholism in 33%, diabetes in 11% and other immunosuppression in 11%.…”
Section: Epidemiology and Risk Factors For Lvad Infectionsmentioning
confidence: 97%
“…Subsequent innovations (axial to centrifugal flow) have not resulted in a reduction in infectious complications [7,8] with an actual increase in sepsis with the Heartware HVAD device compared to HeartMate II control [7]. Studies have looked at factors including age [22], gender [23], body habitus including both small patients [24] and obesity [25], trauma [26], duration of LVAD support [27] as well as presence of comorbid conditions such as diabetes [28][29][30], depression and chronic kidney disease (CKD) [31], alcoholism and immunosuppression [29], and malnutrition ( [32,33] and references therein). In a Japanese multicenter trial looking at 300 patients receiving HeartMate II between April 2013 and December 2016, patients older than 60 had similar overall survival and risk of driveline and pocket infections [22].…”
Section: Epidemiology and Risk Factors For Lvad Infectionsmentioning
confidence: 99%
“…In one recent study, 22.6% of patients with LVAD implantation presented with infectious complications, among which almost a third were caused by P. aeruginosa (3). We present here the high-quality draft genome sequence of a P.…”
Section: Announcementmentioning
confidence: 99%